2020
DOI: 10.1186/s12864-020-06900-8
|View full text |Cite
|
Sign up to set email alerts
|

Breeding history and candidate genes responsible for black skin of Xichuan black-bone chicken

Abstract: Background: Domesticated chickens have a wide variety of phenotypes, in contrast with their wild progenitors. Unlike other chicken breeds, Xichuan black-bone chickens have blue-shelled eggs, and black meat, beaks, skin, bones, and legs. The breeding history and the economically important traits of this breed have not yet been explored at the genomic level. We therefore used whole genome resequencing to analyze the breeding history of the Xichuan black-bone chickens and to identify genes responsible for its uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 89 publications
1
42
0
Order By: Relevance
“…This method can aid in identifying many novel SNPs and QTLs associated with phenotypes of interest. In previous GWAS, imputation from low-density SNP chip genotypes to the WGS level was implemented in chickens ( Huang et al, 2018 ; Li D. et al, 2020 ), pigs ( Yan et al, 2018 ), and cattle ( Höglund et al, 2015 ). Imputed genotypes with sufficiently high imputation accuracy are necessary to obtain reliable results in follow-up analyses, such as GWAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method can aid in identifying many novel SNPs and QTLs associated with phenotypes of interest. In previous GWAS, imputation from low-density SNP chip genotypes to the WGS level was implemented in chickens ( Huang et al, 2018 ; Li D. et al, 2020 ), pigs ( Yan et al, 2018 ), and cattle ( Höglund et al, 2015 ). Imputed genotypes with sufficiently high imputation accuracy are necessary to obtain reliable results in follow-up analyses, such as GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…The weight traits and carcass composition traits were measured in line B as follows: body weight at 42 day of age (BW42), carcass weight (CW), eviscerated weight (EW), whole thigh weight (WThW, weight including feet, and single), thigh weight (ThW, weight with bone, and single), thigh muscle weight (ThMW, single), and the WThW, ThW, and ThMW as percentages of BW42 (WThP, ThP, and ThMP). In addition, the same method ( Li D. et al, 2020 ) was used to calculate the feed intake from 28 to 42 days of age (FI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of two other genes, SLMO2, and TUBB1 were also significantly increased in expression in both skin and muscle tissue from adult fibromelanosis chickens might contribute to the dermal hyperpigmentation phenotype [23] . Analysis of RNA-seq suggested that SLMO2, ATP5e, and EDN3 were differentially expressed between the black and yellow skin groups, combined analysis of genomic data found that EDN3 might interact with the upstream ncRNA LOC101747896 to generate black skin color during melanogenesis [24] . Wang et al study indicated that a T2270C mutation in GNAS gene promoter in chicken is correlated strongly with the skin color traits [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The same animals as for transcriptome and metabolome analyses were used. Total RNAs were extracted from breast muscle, leg muscle and skin tissue of one day aged chickens [30]. Additional le 1: Table S1 describes the gene primers (Invitrogen Biotechnology Co., Ltd., Shanghai, China).…”
Section: Transcriptome Analysismentioning
confidence: 99%